Rehabilitation of the face and temporomandibular joint in systemic sclerosis. (June 2021) - Maddali Bongi, Susanna; Passalacqua, Mauro; Landi, Giovanna; Mikhaylova, Svetlana; Tofani, Lorenzo; Del Rosso, Angela; El Aoufy, Khadija; Baccini, Marco; Matucci-Cerinic, Marco; Melchiorre, Daniela
Background: Systemic sclerosis (SSc) alterations of the face and of the mouth cause aesthetic modifications and disability, impairing self-esteem and quality of life (QoL). The aim of this study was to verify the effects of two rehabilitation protocols on facial mimic and mouth opening. Methods: A total of 47 SSc patients (40 females and 7 males, mean age ± SD 59.08 ± 10.31 years), were consecutively selected: 22 were randomly assigned to protocol 1 [home exercises for temporomandibular joint (TMJ), mimic, masticatory and cervical spine muscles] and 25 to protocol 2 (home exercises and combined physiotherapeutic procedures performed by a physiotherapist). Each treatment had a duration of 12 weeks with a follow up of 8 weeks. TMJ dysfunction, orofacial involvement, disability, QoL, and safety were assessed at enrollment (T0), at the end of the treatment (T1), and at follow up (T2). Results: Both Protocol 1 and Protocol 2 induced significant improvements of some clinical and clinimetric parameters, but better results were obtained with Protocol 2. In the comparison between the effects of Protocol 1 and Protocol 2 at T1 and T2, a significant difference was observed only for Mouth Handicap in SSc [MHISS; Total ( p = 0.00178] and for MHISS Mouth opening ( p = 0.0098) at T1. No significant difference of indices of short-form 36 was observed. Conclusion: The present data suggest that TMJ involvement in SSc may be managed by rehabilitation treatments. The action of a physiotherapist prescribing and personalizing exercises may induce better therapeutic effects.